2009
DOI: 10.1038/ijo.2009.141
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-α2-glycoprotein is involved in regulation of body weight through inhibition of lipogenic enzymes in adipose tissue

Abstract: Context: Zinc-a2-glycoprotein (ZAG) was found to influence lipolysis in adipose tissue and has recently been proposed as a candidate factor in the regulation of body weight. Objective: To elucidate the association of serum ZAG level with body weight and percentage of body fat in normal, obese subjects and high-fat diet (HFD)-induced obese mice. Design: The relationship between serum ZAG and obesity-related parameters was studied in 44 human subjects and 36 mice fed standard food and HFD. Furthermore, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
121
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(146 citation statements)
references
References 26 publications
19
121
2
4
Order By: Relevance
“…60 In contrast, ZAG-overexpressing transgenic mice exhibited decreased body weight and epididymal fat, which was accompanied by a reduction in mRNA levels of fatty acid synthase, acetyl-CoA carboxylase-1 and acyl-coenzyme A: diacylglycerol transferase and the increase in mRNA levels of hormone-sensitive lipase in epididymal adipose tissue. 52 The potential role of ZAG in cholesterol metabolism has also been implicated by a recent study, in which a polymorphism in the ZAG gene is found to be associated with total cholesterol and low-density lipoprotein cholesterol in human subjects. 61 In addition to lipid metabolism, ZAG may be involved in the regulation of adiposity through modulating the production of other adipokines.…”
Section: Zag: a Candidate Gene For Obesitymentioning
confidence: 97%
See 1 more Smart Citation
“…60 In contrast, ZAG-overexpressing transgenic mice exhibited decreased body weight and epididymal fat, which was accompanied by a reduction in mRNA levels of fatty acid synthase, acetyl-CoA carboxylase-1 and acyl-coenzyme A: diacylglycerol transferase and the increase in mRNA levels of hormone-sensitive lipase in epididymal adipose tissue. 52 The potential role of ZAG in cholesterol metabolism has also been implicated by a recent study, in which a polymorphism in the ZAG gene is found to be associated with total cholesterol and low-density lipoprotein cholesterol in human subjects. 61 In addition to lipid metabolism, ZAG may be involved in the regulation of adiposity through modulating the production of other adipokines.…”
Section: Zag: a Candidate Gene For Obesitymentioning
confidence: 97%
“…51 Similar to the findings in genetic models of obesity, a decrease in adipose tissue ZAG mRNA and serum ZAG levels has been reported in mice, in which obesity is induced by a high-fat diet. 52 In human subjects, using a gene profiling approach ZAG transcripts have been reported to be decreased in subcutaneous fat of obese women. 53 ZAG gene and protein expression has also been shown to be downregulated in subcutaneous and visceral adipose tissue of obese men and women in comparison with lean controls.…”
Section: Zag Expression and Body Fat Massmentioning
confidence: 99%
“…Serum ZAG levels have been found to be significantly lower in mice fed a high fat diet than those fed a normal diet (7), as well as in obese humans and mice (8). While ZAG overexpression in mice reduced both the body weight and weight of epididymal fat (8), ZAG knockout animals showed an increased body weight, especially when fed a high fat diet (9). These results suggest that ZAG, like leptin, is closely associated with fat mass.…”
mentioning
confidence: 97%
“…Treatment of ob/ob mice with ZAG decreased body weight and fat mass and improved the parameters of insulin resistance including decreasing plasma levels of glucose, insulin and non-esterified fatty acids (NEFA), improving insulin sensitivity, and increasing muscle mass (6). Serum ZAG levels have been found to be significantly lower in mice fed a high fat diet than those fed a normal diet (7), as well as in obese humans and mice (8). While ZAG overexpression in mice reduced both the body weight and weight of epididymal fat (8), ZAG knockout animals showed an increased body weight, especially when fed a high fat diet (9).…”
mentioning
confidence: 99%
“…Quantitative real-time RT-PCR (qRT-PCR) was performed with SYBR green fluorescent dye using an ABI7500 PCR system (Applied Biosystems, Foster City, CA, USA) as previously described (Gong et al 2009). In brief, 3T3-L1 preadipocytes were plated in 24-well plate with a density of 2 9 10 4 /ml, then differentiated and treated with HSYA as above.…”
Section: Real-time Fluorescence Quantitative Rt-pcr (Rt-qpcr) Analysismentioning
confidence: 99%